Attitude and Perception of Lecturers towards Electronic Journals in Tertiary Institutions in Sokoto State, Nigeria - SULEIMAN, ADAMU YUSUF; BAPPAH , MAGAJI ABUBAKAR (MiddleBelt Journal of Library and Information Science, 2020)
This study examines attitude and perception of lecturers towards electronic journals (e-journals) in tertiary institutions in Sokoto State. Inspite of the relevance e-journals in teaching, learning and research, it had been discover that a number of lecturers in tertiary institutions of Sokoto State were not exposed to electronic journals. A field survey had shown that academics in the institutions under study are more inclined to consulting printed materials such as textbooks, print journals, magazines etc. with little attention to e-journals. This attitude was attributed to the negative perception some of the lecturers have about electronic journals or lack of awareness. This was, therefore, considered a problem worthy of empirical investigation. The study uses survey research design covering eight (8) tertiary institutions in Sokoto State. Questionnaire was used as the instrument for data collection and administered to 329 lecturers. The data collected were analysed, using descriptive analysis through the use of frequencies and percentages. Findings from the study indicate positive attitude and perception by the lecturers towards e-journals, as it established that lecturers perceived e-journals as an important tool for teaching, learning and research activities. Recommendations made include the need for more enlightenment campaign in the aspect of ejournals usage so as to enable the academics appreciate e-journals more as a tool for accomplishing research tasks and academic development.